Bioactive Compounds of Seaweed Sargassum plagyophyllum and Eucheuma cottonii as Lightening Raw Materials - Maretty Twentyna Dolorosa; Nurjanah Nurjanah; Sri Purwaningsih; Effionora Anwar; Taufik Hidayat (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Seaweed is main commodity with abundant amount of Indonesian waters. Seaweed contains naturallybioactive compounds that acts as antioxidant and tyrosinase inhibitor which inhibit melanin formationand the latest approach used to skin lightening. The aim of this research were to determine chemicalcharacterization such as heavy metal, secondary metabolite (phytochemical compounds), moisture, vitaminC and E, antioxidant activity and total plate count (TPC) on dry simplisia and slurry of S. plagyophyllumand E. cottonii. Total microbe of S. plagyophyllum amounted 2.3×102 colony⁄g with moisture content 16,71%and E. cottonii amounted 2.2×103 colony⁄g with moisture content 19.79%. Brown seaweed, S. plagyophyllum,did not contain dangerous heavy metal. Vitamin C value in both spesies of seaweed were 212.95 mg/kg forS. plagyophyllum and 15,95 mg/kg for E. cottonii. Vitamin E of S. plagyophyllum amounted 363.86 mg/kgand 0.23 mg/kg for E. cottonii. IC50 value of S. plagyophyllum was 109 ppm and 130.62 ppm for E. cottonii.S. plagyophyllum slurry contain bioactive compound such as alkaloids, steroids, flavonoids, saponins andtannins. E. cottonii slurry contain bioactive compound alkaloids and terpenoids.